2008
DOI: 10.1007/s00134-008-1128-2
|View full text |Cite
|
Sign up to set email alerts
|

Central venous to mixed venous blood oxygen and lactate gradients are associated with outcome in critically ill patients

Abstract: A strong association exists between positive DeltaSO(2) and Delta[Lac] and survival in critically ill patients. Whether therapy aimed at increasing DeltaSO(2) and Delta[Lac] results in improved ICU survival remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 18 publications
2
20
3
Order By: Relevance
“…While our study was larger in size than the aforementioned one, it was still underpowered to look at survival due to the excellent survival rates in the contemporary cardiac surgical practice. Our own data seemingly contradict the observations by Gutierrez and co-workes [22]. Patients in whom the central venous exceeded the mixed venous saturations (in our study denoted as a negative SvO 2 -ScvO 2 gradient) had inferior indicators of their hemodynamic status.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While our study was larger in size than the aforementioned one, it was still underpowered to look at survival due to the excellent survival rates in the contemporary cardiac surgical practice. Our own data seemingly contradict the observations by Gutierrez and co-workes [22]. Patients in whom the central venous exceeded the mixed venous saturations (in our study denoted as a negative SvO 2 -ScvO 2 gradient) had inferior indicators of their hemodynamic status.…”
Section: Discussioncontrasting
confidence: 99%
“…Gutierrez et al documented an association between a positive ScvO 2 -SvO 2 gradient and survival in a cohort of 106 critically ill patients [22]. The authors suggested that increasingly positive ScvO 2 -SvO 2 gradients reflected superior oxygen utilization [22]. While our study was larger in size than the aforementioned one, it was still underpowered to look at survival due to the excellent survival rates in the contemporary cardiac surgical practice.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…They drew blood samples from the proximal (ScvO 2 ) and distal (SvO 2 ) port of the PAC every 6 hours from the time of PAC insertion until its removal (30.9 Ϯ 11.0 hours) and reported that more survivors had mean positive ΔSO 2 than the deceased (p o 0.01). 23 This result seems to contradict the current study results, but continuous monitoring of ScvO 2 and SvO 2 was not performed in the study performed by Guiterrez et al Continuous monitoring of ScvO 2 and SvO 2 is a critical issue when ΔSO 2 is used as a predictor of clinical implications. If they performed continuous monitoring of ScvO 2 and SvO 2 , the results may have been different.…”
Section: Discrepancy Between Scvo 2 and Svo 2 In Cardiac Surgerycontrasting
confidence: 65%
“…No complications other than transient arrhythmias were observed during the insertion of any catheter. In case of the use of a PA catheter (Criticath SP 5507H TD, Becton Dickinson, Singapore) in the ICU, blood samples were drawn from the proximal port of the catheter as representative of central venous blood (21)(22)(23). All blood samples were analyzed by a co-oximeter (Radiometer ABL800 flex, Copenhagen, Denmark).…”
Section: Methodsmentioning
confidence: 99%